The Influence of Macro Indicators on Non-Performing Financing at Muamalat Bank Indonesia - Syawaluddin S (Al-Ulum, 2024)
This study aims to determine how the effect of the inflation rate and BI rate on Non-Performing Financing at Muamalat Bank Indonesia. This research uses a descriptive method of verification with a type of quantitative research. The source of data in the study is secondary data with data on the Inflation rate and NPF starting from January 2012 to December 2021 per quarter. Based on the results of the study, it was concluded that the research data was declared normally distributed, free from the problems of classical assumptions (multicollinearity, heteroscedasticity, autocorrelation). And the results of the t test (partially) show that the inflation variable does not have a significant effect on Non-Performing Financing (NPF).